Experimental efficiency of a low concentrating CPC PVT flat plate collector. (1st May 2017) - Proell, M.; Osgyan, P.; Karrer, H.; Brabec, C.J.
Graphical abstract: Highlights: A real-size prototype of the CPC PVT flat plate collector was built and tested. The components and the construction of the collector is described. The results of the thermal and PV efficiency of the collector are presented. Further, the incidence angle modifier for thermal and PV efficiency has been measured. Abstract: PVT collectors aim to solar co-generation of electricity and heat. An new concept raises thermal efficiency by concentrating sunlight with CPC reflectors, in order to access a higher number of solar thermal applications. Losses in PV efficiency due to a higher operating temperature are accepted with regard to a higher overall collector efficiency. As a side effect, the concentration lowers the material usage of PV and enables a high efficient thermal coupling of the PV cell to the heat carrying fluid. The work focuses on the construction, as well as on the angle dependent electrical and thermal measurement of the real-size CPC PVT collector prototype ( 1460 mm × 600 mm × 150 mm ). In previous publications, calculations and experiments studied the influence of the CPC reflectors on the PV efficiency. Further, the thermal coupling between PV cell and heat carrier fluid has been measured in a lab experiment. These results, together with transient annual simulations, were considered in the design process of the CPC PVT prototype with an angular acceptance range of ± 25 ° . The experiments were conducted on the outdoor solar test facility at ZAE Bayern in Garching, Germany. The thermal and PV efficiency has been measured with MPP tracking, as well as for open circuit voltage for fluid temperatures up to 107 ° C . It could be shown, that the thermal efficiency while MPP tracking is elevated to 34 % compared to a glazed flat plate PVT with 17 % for collector temperatures 60 K over ambiance. At the same time, the electrical efficiency drops from 15 % cell efficiency to an overall collector efficiency of 9 %, due to the optical setup, temperature effects and a non-uniform flux distribution caused by the reflectors.